(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Corporations and SME are always looking for ways to improve efficiency and effectiveness inorder to achieve and retain a competitive edge in the market. The key to obtaining the intendedoutcomes is the development of intellectual capital, know-what, know-how, and know-why knowledge aswell as comprehending the significance of this information. It is very beneficial for firms to be able toteach and train workers on the job. One approach for workers to acquire and update the informationneeded to carry out their duties is via e-learning. The utilisation of e-learning in businesses is the maintopic of this essay. New kinds of learning are being created by advancements in information andcommunication technology and the present development of e-learning, which are appealing to small andmedium-sized businesses for overcoming conventional constraints including a lack of funding, time,experience, and facilities.